EMPLOYEE CASUALIZATION AND COST REDUCTION IN NIGERIA’S OIL AND GAS AND BANKING SECTORS - Simeon, Edori Daniel; Daniel, Edori Vivian (International Journal For Research In Business, Management And Accounting, 2021)
The policy of employee casualisation has been in practice for a very long period in Nigeria and it cuts across the public and the private sectors. It has been a cause of disagreement between employers of labour and unions/casualised staff yet it is growing on daily basis. This study tends to find out the reason why employers and casual staff are continuing in this slavery practice and many job seekers are searching for such jobs and also find out the relationship between employee casualistion and cost reduction in Nigeria’s oil and gas sector as well as the banking sector. Questionnaires were printed, distributed and retrieved. The retrieved questionnaires were then used to rank the reasons for the continuing of this obnoxious policy of slavery. It was also used to test the relationship between cost reduction (the dependent variable) and employee casualisation (the independent variable). The study find out that in the oil and gas sector the first reason for employee casualisation is cost reduction, access to specialist for specific project was second while risk mitigation and simplified remuneration were third and fourth respectively. In the banking sector, cost reduction was first, simplified remuneration was second while flexibility and access to specialist for specific project were third and fourth respectively. For casualised staff/jobseekers, better than not having job (high rate of unemployment) was ranked first, better than many permanent jobs was second while others and lack of required qualification were ranked third and fourth respectively. The study also revealed the existence of significant and positive relationship between employee casualisation and cost reduction in the oil and gas and banking sectors in Nigeria. The research concluded that this policy of slavery will not end soon since the parties involved are still continuing in it with reasons that they think are good.